Case Report: Catastrophic antiphospholipid syndrome in a pediatric patient after percutaneous treatment of aortic re-coarctation - García Herrera, Iris Paola; Canales Robredo, Carlos; Aboytes Zavala, Magdalena; Merayo Chalico, Javier; Pineda Arzate, Orfanel Sebastian; Colín Ortíz, José Luis; Aparicio Vera, Luis Alberto (Frontiers in Pediatrics, 2024)
A female patient in middle childhood was diagnosed with coarctation of the aorta at one month of age and underwent a successful cortectomy. At 11 years old, she developed re-coarctation, which was managed through interventional cardiology. Shortly after the procedure, she experienced a sudden and severe clinical decline, presenting with hypoperfusion of the lower extremities, gastrointestinal bleeding, acute kidney injury, and pancreatitis. Multiple thrombotic events were identified, prompting an extensive evaluation for thrombophilia. The patient tested positive for antiphospholipid antibodies and was diagnosed with catastrophic antiphospholipid antibody syndrome (CAPS). An aggressive treatment was initiated, yielding a favorable response following discharge; she made a full recovery and continues to be monitored regularly in cardiology and rheumatology clinics.